Respuesta :

9514 1404 393

Answer:

  A. no solution

  B. unique solution: (x, y) = (0, 0)

Step-by-step explanation:

For these problems, you can subtract the second equation from the first to get something of the form ...

  0 = (expression)

The solution of that will tell you the answer.

__

A. (2x +3y) -(2x +3y) = (4) -(9)

  0 = -5 . . . . . . . . no values of x or y will make this true: NO SOLUTION

__

B. (y) -(y) = (6x) -(x)

  0 = 5x

  0 = x . . . . . . divide by the coefficient of x.

  y = x = 0

The unique solution is (x, y) = (0, 0).